Do Computers Call for Training? Firm-level Evidence on Complementarities Between ICT and Human Capital Investments - Thomas Hempell (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
This paper explores whether investments in information and communication technologies (ICT) and firm?sponsored training programmes are complementary. Three approaches are applied to panel data from German service companies for the time period 1994?98. Results for a system of interrelated factor demands indicate that training complements ICT but not other capital goods. SYS?GMM estimates of production functions reveal that ICT capital is most productive if complemented by training measures in skill?intensive firms. Comparing the impacts on productivity and wage costs shows that ICT raise the profitability of training high?skilled employees.
Keywords: J24; J31; D24; C23; 330; Productivity; Training; Information and Communication Technologies; Complementarities; Services; Panel Data; Computergestütztes Verfahren; Informationstechnik; Betriebliche Weiterbildung; Bildungsinvestition; Faktorsubstitution; Schätzung; Theorie; Deutschland